Prevalensi Parasit Gastrointestinal pada Owa Jawa (Hylobates moloch, Audebert, 1797) yang Terancam Punah di Taman Margasatwa Ragunan, Jakarta Selatan - Anisa Putri Sukmaningrum; Luthfiralda Sjahfirdi; Siti Nursheena Mohd Zain (Postgraduate, University of Mataram, 2025)
Primates living in cages are highly susceptible to parasitic infections. Assessing the level of parasitic infection in endangered animals is important to support animal welfare and develop conservation strategies. The infection status of endoparasites in Javan gibbons has been little reported. This study aimed to identify endoparasites and their prevalence in Javan gibbons in Taman Margasatwa Ragunan (TMR). Fecal samples (N=80) were collected from 4 individual Javan gibbons (1 adult male, 2 adult females, and 1 infant male) in October-December 2024. Fecal samples were preserved with 10% formalin solution and analyzed by the formalin-ethyl acetate sedimentation method. As a result, eggs of the order Strongylida, order Rhabditida (Strongyloides sp.), and order Enoplida (Trichuris trichiura) were found. Adult males were positively infected with worms of the Strongylida order, whereas infant males were infected with Strongyloides sp. and T. trichiura with a prevalence of 25%. The endoparasites found in this study are common in captive and wild Javan gibbons. To prevent an increase in infection, direct contact between humans (keepers/visitors) and Javan gibbons should be strictly prevented. This information is useful in developing a health management program for Javan gibbons in TMR as well as completing information related to endoparasites in Javan gibbons in cages.